Answer:
The answer is that x = 6 and y = -6
Step-by-step explanation:
In order to find these values, we can use elimination. To do so, we multiply the first equation by 2 and then add the equations together.
4x + 8y = -24
-4x - 2y = -12
------------------
6y = -36
y = -6
Now that we have this value, we can plug the value into one of the originals and find x.
2x + 4y = -12
2x + 4(-6) = -12
2x - 24 = -12
2x = 12
x = 6
Answer:
a₅=27.
Step-by-step explanation:
1) according to the condition the given subsequence is arithmetic sequence. It means, the a₁=7 and d=5, then
2) a₅=a₁+4*d; => a₅=7+4*5=27.
Answer:
x = 7
y = 8
Step-by-step explanation:
Since the shapes are similar then <B = <F and <A = <E
<B = <F so
10x + 65 = 135 subtract 65 from both sides
10x = 70 divide both sides by 10
x = 7
<A = <E so
4y - 4 = 28 add 4 to both sides
4y = 32 divide both sides by 4
y = 8
Answer:
it would start at 2.2 on the y axis and go up 2.5 and over 1
Step-by-step explanation: